Mesofacial pseudotransposition treatment in female adolescent class II div. Angle with significant protrusion and upper incisors crowding. - Gallardo Moreno, Wenceslao (Revista Universidad de Guayaquil, 2015)
This report describes a brunette girl of 13 years 8 months old,  with Class II malocclusion Div 1 Angle, presents crowding in the anterior maxilla and mandible, also presents pseudotransposition between the canine and lateral upper left incisor, his concern is aesthetics, ATM was free of symptoms, significant protrusion of the upper lip and the lip closure is insufficient, there is persistence of the left superior temporal canine (primary 63), 10 mm overjet , overbite 50 %. She was treated with removal of the first two upper premolars, the maxillary left canine distalisation pseudotransposition with Ladany spring and later retruded anterior superior steel arches with 4 keys .The interincisive angle was improved from 110 ° to 133 ° and the upper tooth protrusion of 13 mm in relation to the APg line, reduced to 7mm. The overjet and overbite maintain the average value, the curve of Spee was leveled, lower third molars were removed, but the upper third molars were maintained. Records pre and post- treatment are Facial change was large and good alignment and symmetry of the dental arch, the cuspid pseudotransposición was properly positioned in the dental arch, the ATM was free of symptoms. Logs after  three and a half years, showed a good occlusion and long term stability. There are no symptoms in the  TMJ, the canine and posterior disclusion is optimal, the result is stable and very good prognosis Keywords: Class II, Div 1, transposition, pseudotransposition.
Keywords: Class II; Div 1; transposition; pseudotransposition